Magnetothermal Miniature Reactors Based on Fe3O4 Nanocube‐Coated Liquid Marbles. Issue 6 (20th January 2021) - Li, Hualin; Liu, Peng; Gunawan, Renardi; Simeneh, Zemenu Mengistie; Liang, Chen; Yao, Xi; Yang, Mengsu
Abstract: Liquid marbles have recently attracted much interest in various scientific fields because of their isolated environment and robustness. However, conventional liquid marbles lack a reliable heating mechanism, which is critical in many potential applications. Here, the development of iron oxide (Fe3 O4 ) nanocube‐coated liquid marbles (iNLMs), which can be homogeneously heated with an alternating magnetic field (AMF) to as high as 86 °C, is reported. Through tuning the power of the AMF, the iNLMs canbe heated to desired temperatures in controllable patterns. Furthermore, multicenter and selective heating is realized based on the unique magnetothermal properties of iNLMs. As heatable miniature reactors, the iNLMs are further demonstrated to facilitate the kinetic study of temperature‐dependent chemical reactions. DNA amplification is successfully performed in liquid marbles, achieving a 25% superior amplification rate compared with that in a common thermal cycler. These results confirm the feasibility of coating liquid marbles with Fe3 O4 nanocubes to form delicate magnetothermal miniature reactors, which provides a reliable method of applying liquid marbles in areas such as biosensor technology, point‐of‐care testing, and theranostics. Abstract : The novel development of AMF‐heatable iron oxide nanocube‐coated liquid marbles is reported, which incorporates a reliable heating mechanism and is shown to successfully perform DNA amplification with better efficiency than standard thermal cycler. This report demonstrates the potential development of liquid marbles as heatable mini‐reactors and their applications in areas such as biosensor, point‐of‐care testing, and theranostics.